"Kot divji, hrzajoči konj / prihaja k nam svoboda!" - Vičar, Branka (Studia Historica Slovenica, 2016)
This article is theoretically based on critical animal studies and reveals the ways in which the horse was represented in Slovenian partisan art. The analysis shows two complementary roles of the horse in partisan art: 1) figurative role with which the idea of rebellion and revolution is emphasised, 2) the role of the subject, which puts the horse in a relation with a partisan in the national liberation struggle. The subjectivity of the horse is made up of the recognition and acknowledgment of the horse%s emotions, feeling and experiences, but the horse with these acknowledgments is not necessarily constructed as an autonomous subject. The equality between the partisan and the horse is established only in cases when they are presented as comrades in the struggle.
Keywords: druga svetovna vojna; konji; likovna umetnost; likovni motivi; literarni motivi; slovenska književnost; slovenska umetnost; svetovna vojna 1939-1945